PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN PT. SUZUKI FINANCE INDONESIA CABANG BALIKPAPAN - Rahmadaniah; Harmayanto; Achmad Afrianoor Firdaus (PIRSAP (Paser Institute for Scientific Research and Publications), 2023)
This study aims to determine the effect of work stress on employee performance at PT. Zusuki Finance Indonesia Balikpapan Branch. The research location was carried out at PT. Suzuki Finance Indonesia Balikpapan Branch. The purpose of this study was to determine the effect of work stress which includes individual stress variables (X1), environmental stress (X2), organizational stress (X3), on employee performance (Y) at PT. Suzuki Finance Indonesia Balikpapan Branch. The analytical tool used is multiple linear regression analysis which is processed with the help of SPSS (Statistical Packages For Social Sciences). From the research results, the validity test results were obtained from the number of questions as many as 13 items, all of which had an rcount value that was more than rtable = 0.355, which meant that all questions were valid. From the results of the reliability test, it can be seen that a result of 0.905 is obtained, which means that the questionnaire items can be said to be reliable (proper) because Cronbach's Alpha > 0.6. Regression equation Y = 0.678 – 0.138X1 + 0.225X2 + 0.687X3. The magnitude of the correlation coefficient (R) is 0.924. This shows that there is a strong relationship between the variables Individual Stress (X1), Environmental Stress (X2), Organizational Stress (X3), on Employee Performance (Y) at PT. Suzuki Finance Indonesia Balikpapan Branch. While the coefficient of determination (R2) is 0.853. This shows that 85.3% of the variation or change in the value of the dependent variable (employee performance) can be explained by the independent variable (work stress) consisting of individual stress (X1), environmental stress (X2), and organizational stress (X3), then 14.7% is influenced by other variables not included in this study.